"The World is a Maze of Illusions." Peripheral Religion and Enchantment in Cyberpunk 2077 - Moyzhes, Leonid (Gamevironments, 2025)
In this article, we examine peripheral religion and the peripherality of religion in Cyberpunk 2077 (2020). From a hermeneutic analysis of the game’s narrative and mechanical elements, we argue that - despite the secular register of the game’s techno-dystopian setting - the underlying enchantment of the gameworld subtly reinforces the epistemic legitimacy of otherwise peripheralized religious practices and beliefs. We begin with an overview of key theoretical concepts concerning simulation, representation, and enchantment that converge at the core of our argument. Following this, we situate Cyberpunk 2077’s gameworld within the longer literary history of cyberpunk as a genre of speculative fiction and conclude with a close reading of the tarot-themed questline Fool on the Hill that runs parallel to the game’s main narrative. Our analysis illustrates the complicated relationships between the game’s fictional setting, its mechanics and rules, and the game’s status as a simulation of an enchanted world, which together invite players to reflect on peripheral religion in a present day characterized by the secularizing spectre of the Enlightenment.